2001
DOI: 10.1034/j.1600-0528.2001.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

The decline in dental caries among Belgian children between 1983 and 1998

Abstract: A remarkable decline in dental caries was observed during the 15-yr period. The factors related to the children's home-based and professional dental health care were associated with the observed decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1
6

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 15 publications
4
39
1
6
Order By: Relevance
“…7 Occlusal caries accounts for the majority of affected tooth surfaces in adolescents and adults. [8][9][10][11] It is, therefore, apparent that preventing dental caries on the occlusal surfaces of FPMs is a key objective in preventative dental care. These surfaces represent the surfaces most susceptible to decay and are present in susceptible children.…”
Section: Teeth At Risk Of Dental Cariesmentioning
confidence: 99%
“…7 Occlusal caries accounts for the majority of affected tooth surfaces in adolescents and adults. [8][9][10][11] It is, therefore, apparent that preventing dental caries on the occlusal surfaces of FPMs is a key objective in preventative dental care. These surfaces represent the surfaces most susceptible to decay and are present in susceptible children.…”
Section: Teeth At Risk Of Dental Cariesmentioning
confidence: 99%
“…Thus, the use of a method capable of identifying spot lesions and their progression over time in an epidemiological level may be relevant considering the objective to be achieved in a study. The need for operative treatment at the population or individual level may be measured by the DMF index (11)(12)(13). While this information is in itself important, when evaluated alone, it perpetuates the over past concept that the caries process should be treated by restorations and extractions only.…”
Section: Introdutionmentioning
confidence: 99%
“…Some recent studies have shown that people in developing countries were found to have high caries prevalence for all age groups compared with developed countries (Bolin et al, 1996;Carvalho et al, 2001;Christensen et al, 2003;Gibson et al, 1999;Güçiz and Gökalp, 2008;Sheiham, 2005;Unlüer et al, 2007). According to those studies conducted in a developing country to estimate prevalence and severity of oral and dental health problem, more than half of the individuals had dental caries and the prevalence of normal population without a toothbrush was 15.9%, the toothbrushing rate 2 to 3 times daily was 22.2 and 27.6% in adults and geriatric peoples, respectively Güçiz and Gökalp, 2008;Unlüer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It is a well known fact that, brushing teeth significantly reduces the risk of dental caries and as the frequency of toothbrushing decreased, the tooth decay increased (Carvalho et al, 2001;Gibson and Williams, 1999). According to a recent study (Fujita et al, 2009) lower frequency of daily tooth brushing was related to higher prevalences of diabetes mellitus, hypertension and high triglyceride (TG) and/or low high density lipoprotein cholesterol (HDL-C).…”
mentioning
confidence: 99%